PENDAMPINGAN PERAN DAN POTENSI KEAGAMAAN, SOSIAL DAN EKONOMI DI DUSUN KARANGSEMI KECAMATAN GONDANG KABUPATEN NGANJUK - Arofik, Slamet; Fitri, Abdul Basith Misbahul; Nadhif, Muchammad; Huda, Afiful (Janaka, Jurnal Pengabdian Masyarakat, 2018)
Karangsemi village Gondang Subdistrict is one of the villages in Nganjuk Regency which has the potential to become one of the developing and developed villages. One factor that causes this is ownership of existing human resources. However, because the SDA is not optimal it causes the village to be unable to become a village that has a "lighthouse" that can be known by anyone. By carrying out the ABCD approach, Community Service (PKM) conducted by STAI Darussalam lecturers, assisted by students, launched programs in order to improve natural resources. Through assistance including religious, economic and social, it is hoped that this village will be able to develop and be ready to compete with other villages.